معوقات تطبيق الصيرفة الإلكترونية في فروع المصارف التجارية الخاصة العاملة في مدينة اللاذقية - ضاهر حنان (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الورقة إلى دراسة معوقات تطبيق الصيرفة الإلكترونية في فروع المصارف التجارية الخاصة العاملة في مدينة اللاذقية. وقد قدمت هذه الورقة نموذجاً لخمس معوقات محتملة ركزت على مايلي: البنية التحتية، المعوقات الأمنية والقانونية، المعوقات الاجتماعية والثقافية، المعوقات الاقتصادية و المعوقات التقنية والفنية. لتحقيق هدف الدراسة جمعت البيانات استناداً إلى استبانة صممت خصيصاً لهذا الغرض. وقد وزعت على 65)) من المدراء والخبراء في مجال الصيرفة الإلكترونية. ومن أجل تحليل البيانات استخدم برنامج الحزمة الإحصائية للعلوم الاجتماعية Statistical Package for Social Sciences والمعروف اختصاراً (SPSS). وقد استخدمت مجموعة من الأساليب الإحصائية كالنسب المئوية، واستخدم اختبار كاي مربع لاختبار الفرضيات. أظهرت النتائج أن المعوقات الاجتماعية والثقافية جاءت في المرتبة الأولى، وفي المرتبة الثانية جاءت المعوقات التقنية والفنية، يليها في المرتبة الثالثة العوامل الأمنية والقانونية، وفي المرتبة الرابعة جاءت المعوقات الاقتصادية، وأخيراً معوقات البنية التحتية. The purpose of this Paper is to study the challenges in the implementation of electronic banking in the branches of private commercial banks operating in Latakia. This paper provides a possible five challenges model centered upon the following: infrastructure, legal-security, socio-cultural, economic, and technology and technical obstacles. To achieve this purpose, data were collected based on a questionaire specially designed for this purpose. it was distributed to 65 managers and experts familiar with electronic banking. for data analyses was used the Statistical Package for the Social Science (SPSS). It has been used some statistical methods like percentages and Chi- square test to examine the hypotheses. The results showed that that socio-cultural obstacles has placed one, second is technology and technical obstacles, third legal-security factors, fourthly economical obstacles and the last is infrastructure obstacles.